The Role of Factors in Business-to-Business E-Procurement Implementation - Naseebullah, M.; P.D.D., Dominic; Hassan, M.F. (2010)
With the advent of internet organizations are facing global competition to improve their efficiency in terms of cost reduction and services delivery. The organizations are forced to shift their operations from traditional to a virtual E-procurement. E-procurement is persistently receiving attention from industries, business and government agencies and becoming one of today's most widespread IT solutions for business procurement operations. However, not every firm has been successful in E-procurement implementation. A number of factors have been identified to hinder E-procurement implementation, especially within the context of Business to Business (B2B). This paper attempted to provide a comprehensive survey on existing literature with regards to this issue. Eventually, a proposed classification is developed that consolidates all the relevant factors which have been categorized into organizational, technological and environmental perspective.